Race, ethnicity, and support for climate policy. (1st November 2022) - Benegal, Salil; Azevedo, Flávio; Holman, Mirya R
Abstract: Addressing the increasing temperatures of the globe requires society-wide adaptation and mitigation efforts. One central challenge to these efforts is the resistance of groups to support broad policy efforts to reduce global temperatures, with particular resistance in the United States. While scholars have established that partisanship, ideology, demographic, and socio-economic characteristics shape support for climate policy, we do not yet understand how these factors might vary within and across racial and ethnic groups. In this paper, we use pooled data from the Cooperative Election Study ( N total = 241 800) to examine differences in attitudes about climate policy between Asian, Black, Hispanic, and white Americans. Comparing across groups, we demonstrate that the many core findings of scholarship on support for climate policy apply nearly exclusively to white Americans, with varying correlational relationships for Asian, Black, and Hispanic Americans. Our efforts provide a much-needed examination of how racial identity shapes views on climate change and show that central, replicated results in scholarship on climate change apply largely to the views and behaviors of white Americans.